The Analysis Study of Prevalence, Diagnosis, and Management of Cataract in Adult Eye: A Comprehensive Systematic Review - Dunand, Muhammad Luthfi; Dunand, Indira Ulfa; Hadi, Indra (International Medical Journal Corp. Ltd, 2024)
Background: Cataract remains a major cause of visual impairment worldwide. However, in many countries cataract surgery is easily available. Cataract surgery is a kind of effective way to deal with cataract, but it is acompanied with many surgical complications and expensive costs that present enormous social and economic problems to a society, especially in the remote and poor areas of developing countries. The aim: The aim of this study to show about prevalence, diagnosis, and management of cataract in adult eye. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. Result: Eight publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Cataracts to increase in the near future due to an increase in the aging population and pre-senile cataracts. The current study also provides clinical determinants for cataract and cataract surgery. Since cataract has emerged as a public concern and the cost burden for cataract surgery has increased with an aging population, it is expected that the present study will form a cornerstone for further investigations and the establishment of a public health plan.